Pertanggungjawaban Pidana Korporasi Dalam Tindak Pidana Korupsi Proyek Infrastruktur Pendidikan: Kasus Pembangunan Gedung FKIK Universitas Jambi - Pratama, Putra Yudha (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
Corruption Crimes (Tipikor) involving corporations in educational infrastructure projects are a serious threat to the quality of national development. This study aims to analyze and identify the corporate criminal liability model applied by judges in the corruption case of the construction of the Faculty of Medicine and Health Sciences (FKIK) University of Jambi (Unja) Building, as well as to test the effectiveness of additional criminal sanctions imposed. This normative-empirical legal research uses a case study approach to the Jambi Corruption Court Decision. Primary data in the form of decisions were analyzed qualitatively, supported by a study of the corporate criminal law literature. The results of the study show that the panel of judges tends to use the Identification Doctrine by applying the principle of